The Relative Antithrombotic Effectiveness of Heparin, a Low Molecular Weight Heparin, and a Pentasaccharide Fragment in an Animal Model - Thomas, D P; Merton, R E; Gray, E; Barrowcliffe, T W (Thrombosis and Haemostasis, 1989)
The antithrombotic efficacy of unfractionated heparin (UFH), a low molecular weight heparin (LMWH) and a synthetic pentasaccharide (PENTA) has been compared in an animal model for stasis thrombosis. We have also compared the relative ability of these three agents to impair thrombin generation in vitro and in vivo, and measured their effects on anti-Xa activity and thrombin clotting times. UFH, LMWH and PENTA all had the capacity to impair thrombogenesis, although there were marked differences in their relative effectiveness. Reduction of thrombin generation to 20% of control values was closely correlated with the prevention of thrombosis after 20 minutes’ stasis, but this was only achieved with UFH. The same dry weight dose of LMWH or PENTA reduced thrombin generation to about half control values, and neither significantly impaired thrombus formation after 20 minutes’ stasis. Impaired thrombin generation correlated better than anti-Xa activity with prevention of stasis thrombosis. In this model, UFH was clearly superior to LMWH and PENTA as an antithrombotic agent.
Keywords: Heparin; Low molecular weight heparin; Pentasaccharide; Thrombosis; Thrombin generation